Sosialisasi Kewirausahaan Berbasis Online Untuk Meningkatkan Minat, Motivasi, Dan Kreativitas Siswa/i - Dona Listianawati; Aqil Rosyid; Bella Bella; Sheila Ardianti (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Technological developments in the digital age such as today grow faster by the day, month by month, to the next year. Internet use has always been used in various areas of life. The Internet is available to everyone, including entrepreneurs for business development efforts. Many entrepreneurs can rely on business from Internet transactions. In the 2013 education curriculum, entrepreneurship is taught to all high school students to shape student mindset, attitude, and behavior into an early entrepreneur. To support this government program and benefits technology, basic online business training USES only phones that are currently very close to our daily lives. Training takes place at SMAN 17 Kab. Tangerang with 22 students. These methods of carrying out this activity involve material exposure, discussion, and end with a question and answer session. This activity has a positive impact on knowledge and insight on online business so that students can develop potential. This can be learned from their enthusiasm for the material being presented. The objectives in this activity include students' knowledge and understanding of the online business and being motivated to start a business through e-commerce. Moreover, students can be graduates who have skills in business.